2011
DOI: 10.1007/s11250-010-9775-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of strain and different skip-a-day feed restriction periods on the growth performance of broiler chickens

Abstract: The effects of 6, 10 and 14 days of skip-a-day feed removal during the starter and grower periods on the growth performance of Ross 308 and Hubbard broiler chickens were studied in a 49-day production period. Ross 308 was superior to Hubbard in weight gain, market weight and feed utilization but consumed more feed, deposited more abdominal fat and had a higher mortality rate. Overall, feed removal improved feed efficiency, had insignificant effects on abdominal fatness and mortality rate and reduced feed intak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 19 publications
2
7
0
Order By: Relevance
“…The higher feed intake, faster growth and heavier market weight of Ross 308 than Hubbard during the postrestriction period despite the similarity in feed conversion ratio suggests that Ross 308 is superior to Hubbard in post-restriction growth rate and final body weight but needs more feed to maintain this superiority as suggested by the positive genetic correlations among feed intake, growth rate and body weight. The superiority of Ross 308 over Hubbard in these traits has also been reported in an earlier study by Benyi et al (2011). Also, the fact that the birds whose feeding times were reduced by 4 and 6 days converted feed more efficiently, gained more weight than the ad libitum controls and had similar 49-day weights as the controls suggests that the 4-and 6-day feed-restricted birds had compensatory growth during realimentation.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The higher feed intake, faster growth and heavier market weight of Ross 308 than Hubbard during the postrestriction period despite the similarity in feed conversion ratio suggests that Ross 308 is superior to Hubbard in post-restriction growth rate and final body weight but needs more feed to maintain this superiority as suggested by the positive genetic correlations among feed intake, growth rate and body weight. The superiority of Ross 308 over Hubbard in these traits has also been reported in an earlier study by Benyi et al (2011). Also, the fact that the birds whose feeding times were reduced by 4 and 6 days converted feed more efficiently, gained more weight than the ad libitum controls and had similar 49-day weights as the controls suggests that the 4-and 6-day feed-restricted birds had compensatory growth during realimentation.…”
Section: Discussionsupporting
confidence: 77%
“…This suggests that genotype × environment interaction measured in this study as strain × feeding regime interaction may have important influences on mature body weight and probably weight gain but not on other traits. Benyi et al (2011) reported significant strain × feeding regime interactions effects on 35-day weight, weight gain and feed intake. The significant differences between the strains in feed intake, growth rate and market weight during the entire study period have been previously reported (Rosa et al, 2007) but other authors such as Dozier et al (2003) reported insignificant differences among strains of broilers in response to skip-a-day feed restriction.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Feed restriction programmes were initially used to reduce the incidence of infectious, metabolic and skeletal disorders that result from the high growth rate of broilers (Benyi, Acheampong‐Boateng, & Norris, ; Lee & Leeson, ). It was also used as an alternative method to decrease broiler mortality in high temperature conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the overall performance also agree with the findings of Urdaneta-Ricon and Lesson (2002), Dozier et al (2002Dozier et al ( , 2003, and Khajali et al (2007) who stated that broiler chickens are able to compensate for loss of weight resulting from short periods of feed restriction at early age, and do not follow the findings of De Silva and Kalubowila (2012) who found significant reduction in body weight at 42 days old after 3 h fasting per day from 21 to 42 days old. The in significant differences in overall performance between the control and fasted birds is supported by the findings of Navidshad et al (2006), Mohebodini et al (2009) and Benyi et al (2011). Acheampong-Boateng et al (2012) found that feed restriction birds could not recover from the slow growth during restriction and they were lighter than the control group.…”
Section: Overall Performancementioning
confidence: 57%